APPLIED MECHANICS FOR MARINE ENGINEERS - Russell, Paul A. (Reeds marine engineering and technology, 2021)
This book covers the principal topics in applied mechanics for professional trainees studying Merchant Navy Marine Engineering Certificates of Competency (CoC) as well as the core syllabi in applied mechanics for undergraduates studying for BSc, BEng and MEng degrees in marine engineering, naval architecture and other marine technology related programmes. This new edition has been fully updated to reflect the recent changes to the Merchant Navy syllabus and current pathways to a sea-going engineering career, specifically the increased emphasis that has been placed on colleges and universities now responsible for the academic requirements for those studying for a career in marine engineering. In particular this means the book has been updated to include more information about the general principles and applications of the exercises in the practical world of marine engineering. Each chapter has fully worked examples interwoven into the text, with test examples set at the end of each chapter. Other revisions include examples reflecting modern machines and practice, current legislation and current syllabi